Synthesis and characterization of CoFe2O4 magnetic nanotubes, nanorods and nanowires. Formation of magnetic structured elastomers by magnetic field-induced alignment of CoFe2O4 nanorods - Antonel, Paula Soledad (2015)
Magnetic CoFe2O4 nanotubes, nanorods and nanowires were synthesized by the template method. The materials are highly crystalline and formed by compactly packed ceramic particles whose equivalent size diameter depends on the nanostructure type. Nanotubes and nanorods present the remarkable characteristic of having very large coercive fields (1000-1100 Oe) in comparison with nanoparticles of the same crystallite size (400 Oe) while keeping similar saturation magnetization (53-55 emu/g). Nanorods were used as filler material in polydimethylsiloxane (PDMS) elastomer composites, which were structured by curing in the presence of uniform magnetic field, Hcuring. In that way the nanorods agglomerate in the cured elastomer, forming needles-like structures (pseudo-chains) oriented in the direction of Hcuring. SEM analysis show that pseudo-chains are formed by bunches of nanorods oriented in that direction. At the considered filler concentration (1 % w/w), the structured elastomers conserve the magnetic properties of the fillers, that is, high coercive fields without observing magnetic anisotropy. The elastomer composites present strong elastic anisotropy, with compression constants about ten times larger in the direction parallel to the pseudo-chains than in the perpendicular direction, as determined by compression stress-strain curves. That anisotropic factor is about three-four times higher than that observed when using spherical CoFe2O4 nanoparticles or elongated Ni nanochains. Hence, the use of morphological anisotropic structures (nanorods) results in composites with enhanced elastic anisotropy. It is also remarkable that the large elastic anisotropy was obtained at lower filler concentration compared with the above mentioned systems (1 % w/w vs. 5-10 % w/w).